307 Sleep and occupational wellbeing in active duty U.S Army Soldiers. (3rd May 2021) - Pirner, Maddison; Doyle, Scott; Mantua, Janna; Bessey, Alexxa; Naylor, Jacob; Ritland, Bradley; Sowden, Walter; Burke, Tina; Mckeon, Ashlee
Abstract: Introduction: Insufficient sleep is ubiquitous among active duty service members in operational settings. Although insufficient sleep has been linked to poor cognitive, psychological, and physiological outcomes in military populations, little research has investigated the impact of insufficient sleep on Soldier occupational wellbeing. This study examined the longitudinal association between sleep quality and occupational functioning in a population of active duty U.S. Army Soldiers. Methods: Sixty male Soldiers (age 25.41±3.74 years) participated. Sleep quality and occupational outcomes were assessed four weeks apart (before and after an annual training mission). Sleep quality was assessed using the Pittsburgh Sleep Quality Index (PSQI). Occupational outcome measures included the Emotional Exhaustion Scale, Walter Reed Functional Impairment Short Scale, Role Overload Scale, and Perceived Stress Scale. Linear regressions assessed the prediction of PSQI Global Score on occupational outcome scores. Student's t-tests compared occupational outcomes between "good" and "poor" sleepers (PSQI Global Score > 5 = poor sleeper). Results: Poorer sleep quality at baseline broadly predicted poor occupational outcomes post-training. Specifically, higher PSQI Global Scores predicted higher emotional exhaustion (B = 1.6, p < 0.001, R2 = 0.25), functional impairment (B = 0.29, p < 0.03, R2 = 0.14), role overload (B = 28, p < 0.008, R2 = 0.12), and perceived stress (B = 0.34, p < 0.004, R2 = 0.2). Furthermore, occupational outcome scores were significantly higher in poor sleepers than good sleepers: emotional exhaustion: (t(58) = -4.18, p < .001); functional impairment: (t(59) = -3.68, p = .001); role overload (t(58) = -3.20, p = .002); and perceived stress (t(58) = -2.43, p = .02). Conclusion: This study identified a longitudinal relationship between sleep quality and occupational outcomes, suggesting that service members with poor sleep may be at risk for experiencing poor workplace wellbeing. Given the association between service member wellbeing and likelihood to re-enlist, insufficient sleep may negatively impact Soldier attrition. Future studies should aim to augment sleep quality and track occupational outcomes in this population. Support (if any): This work was funded by the Military Operational Medicine Research Program of the United States Army Medical Research and Development Command.